2011
DOI: 10.1007/s00520-011-1084-1
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotics in palliative medicine—results from a prospective epidemiological investigation from the HOPE survey

Abstract: The initiation of therapy seems to be easier than withdrawing and withholding, as involvement of other team members in the decision-making process was then sought more often. When antibiotics were given until death, the indication should be reconsidered because of a possibly undesirable prolongation of the dying process. Clinical practice may benefit from clear definitions of treatment goals and outcome criteria to better evaluate the necessity for and success of antimicrobial treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
47
0
18

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(68 citation statements)
references
References 18 publications
(24 reference statements)
3
47
0
18
Order By: Relevance
“…Similar results were reported in other studies where forgoing medication (including antibiotics) occurred more frequently in patients aged above 80 20 35. The use of antibiotics in palliative care is still debated and considered an important ethical challenge, requiring clarification of the goals for administering them at this stage 36. These aims might be to provide comfort rather than treat the infection.…”
Section: Discussionsupporting
confidence: 83%
“…Similar results were reported in other studies where forgoing medication (including antibiotics) occurred more frequently in patients aged above 80 20 35. The use of antibiotics in palliative care is still debated and considered an important ethical challenge, requiring clarification of the goals for administering them at this stage 36. These aims might be to provide comfort rather than treat the infection.…”
Section: Discussionsupporting
confidence: 83%
“…We examined the magnitude of antibiotic use in a nationally representative sample of hospice patients and observed that 27% of hospice patients received antibiotics in the last seven days of life. Although lower than previous estimates of antibiotic utilization in hospice patients, which ranged from 36%-84%, those studies focused on specific patient subgroups, e.g., cancer patients, and examined antibiotic utilization for the entire duration of hospice care (3, 11-13). …”
Section: Discussionmentioning
confidence: 95%
“…Several studies have reported on the discomfort experienced by advanced dementia patients, describing an increase in distressing symptoms, such as pneumonia, fever and eating problems . In the literature, there has been much debate on the use of medical treatments, such as antibiotics in palliative care, even though antibiotic treatment is not usually cited among the main ethical challenges of end‐of‐life care …”
Section: Introductionmentioning
confidence: 99%